The Equality Equation : Advancing the Participation of Women and Girls in STEM - Hammond, Alicia; Rubiano Matulevich, Eliana; Beegle, Kathleen; Kumaraswamy, Sai Krishna (World Bank, Washington, DC, 2020)
Science, technology, engineering, and mathematics (STEM) are vital to the economic and social prosperity of countries. Yet, women and girls continue to be underrepresented in STEM careers, although there is wide variation among countries and across STEM fields. Beyond income disadvantages for women because they have less access to STEM careers, the gender gap in STEM is also a missed opportunity for economies and an inefficient allocation of labor and talent. This report explores the participation of women and girls relative to men and boys in STEM-related education and employment through a global, comprehensive review of the evidence. The report focuses on both the drivers and the solutions related to the participation of women and girls in STEM.